Influence of exercise and emotional stresses on secretion of prolactin and growth hormone in Thoroughbred horses - KITAURA, Tomoki (J Equine Sci, 2021)
The secretion of prolactin and growth hormone in response to exercise and emotional stresses was investigated in Thoroughbreds. Two experiments were performed: one with loading of only exercise stress and one with simultaneous loading of exercise and emotional stresses. Exercise stress was loaded in 4 steps using a treadmill for horses: pre-exercise period (5 min), walking period (6.5 min), galloping period (3 min), and cooling down period (10 min). Emotional stress was loaded by showing a loud video of an audience at a racetrack during the walking period. The results clearly demonstrated that exercise stress rapidly increased the secretion of prolactin and growth hormone and that secretion of them persisted for a specific period after the exercise. In addition, emotional stress promoted prolactin secretion.